Evolution of surface topography and optical band gap of ZnO film deposited on NiO/Si(100). (19th December 2017) - Das, P. K.; Biswal, R.; Choudhary, R. J.; Ganesan, V.; Mallick, P.
Abstract : Evolution of surface features and optical band gap of ZnO thin films deposited on different NiO/Si(100) are reported. In order to create different initial microstructure, we first deposited NiO film on Si(100) at 3 different temperatures (400°C, 650°C, and 700°C) by pulsed laser deposition. These NiO/Si(100) films are used as substrate for the deposition of ZnO films. Combining the results obtained from grazing incidence X‐ray diffraction, atomic force microscope, and UV‐Visible characterization, our study indicated that the microstructure of the substrate takes the important role in dictating properties of the film. Our study also indicated that one needs to choose appropriate synthesis condition to achieve good quality ZnO films.